2016
DOI: 10.1080/15564886.2016.1196283
|View full text |Cite
|
Sign up to set email alerts
|

Victim Offender Overlap: Dual Trajectory Examination of Victimization and Offending Among Young Felony Offenders Over Seven Years

Abstract: The relationship between victimization and offending has been shown consistently across different samples, settings, and crime types. This study uses data from the Pathways to Desistance Study to examine dual trajectories of offending between the ages of 15 and 24 in a sample of male felony offenders. The dual trajectory models demonstrate substantial convergence in victimization and offending. And while there are sizable numbers of youth who continue to be victimized, but desist or decrease in their offending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 75 publications
1
36
0
Order By: Relevance
“…Furthermore, few conventional routine activities protect against victimization and none eliminate the strong positive effects of delinquent behavior (Lauritsen, Laub, & Sampson, 1992). On the other hand, research-based trajectory models of victimization and offending found that risky lifestyle measures were the most reliable determinants of membership in the dual trajectory groups (Mulford et al, 2016).…”
Section: Revisiting Leading Theoretical Perspectivesmentioning
confidence: 99%
“…Furthermore, few conventional routine activities protect against victimization and none eliminate the strong positive effects of delinquent behavior (Lauritsen, Laub, & Sampson, 1992). On the other hand, research-based trajectory models of victimization and offending found that risky lifestyle measures were the most reliable determinants of membership in the dual trajectory groups (Mulford et al, 2016).…”
Section: Revisiting Leading Theoretical Perspectivesmentioning
confidence: 99%
“…Stewart, Gossop, Marsden, & Rolfe, 2000). Although victim and offender roles overlap in a number of populations (Flexon, Meldrum, & Piquero, 2015;Jennings, Higgins, Tewksbury, Gover, & Piquero, 2010;Mulford et al, 2016;Mustaine & Tewksbury, 2000;Posick, 2013;Silver, Piquero, Jennings, Piquero, & Leiber, 2011;TenEyck & Barnes, 2017), including substance users (Darke, Torok, Kaye, Ross, & McKetin, 2010;French et al, 2004;McCOY, Messiah, & Yu, 2001), substance users are often described either in terms of their offending or their status as victims. The relationship between substance use and victimization may be simplified by not taking into account how the victim and offender roles are intertwined (Lauritsen, Sampson, & Laub, 1991;Reingle, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Victimization by aggression and violence is a prevalent theme in the autobiographies of perpetrators of violence, including convicted offenders (e.g., Jennings et al, 2012;Mulford et al, 2018). Across one's lifetime, the risk of victimization appears highest during adolescence (Cops & Pleysier, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The considerations raised above led us to sample our data in sentenced offenders as well as in adolescents from the general community. There is, generally, a high rate of victimization among individuals who are sentenced for violent offences (e.g., Dutton & Hart, 1992;Jennings, Piquero, & Reingle, 2012;Mulford et al, 2018;Widom, 1989). Furthermore, the risk of becoming the victim or perpetrator of injustice or aggression appears to peak in adolescence (Cops & Pleysier, 2014).…”
Section: With the Consent Of Mccullough And Karremans (Personal Commumentioning
confidence: 99%